2003
DOI: 10.1007/s00442-003-1198-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of NDVI, biomass, and ecosystem gas exchange to long-term warming and fertilization in wet sedge tundra

Abstract: This study explores the relationship between the normalized difference vegetation index (NDVI), aboveground plant biomass, and ecosystem C fluxes including gross ecosystem production (GEP), ecosystem respiration (ER) and net ecosystem production. We measured NDVI across long-term experimental treatments in wet sedge tundra at the Toolik Lake LTER site, in northern Alaska. Over 13 years, N and P were applied in factorial experiments (N, P and N + P), air temperature was increased using greenhouses with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
164
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(194 citation statements)
references
References 55 publications
(75 reference statements)
23
164
2
3
Order By: Relevance
“…Previous attempts at relating an optical vegetation index (NDVI) to above-ground phytomass for this environment were mixed [9], with r 2 values for Cape Bounty of 0.55. Other studies have found stronger relationships [3,37,59], but were at much coarser spatial resolutions. To show that the ANN results (estimated SAVI values from SAR variables) can be used to predict actual ground-based measures of above-ground phytomass, regression analyses were used with field-sampled values of above-ground phytomass collected for previous research [9].…”
Section: Vegetation Modelingmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous attempts at relating an optical vegetation index (NDVI) to above-ground phytomass for this environment were mixed [9], with r 2 values for Cape Bounty of 0.55. Other studies have found stronger relationships [3,37,59], but were at much coarser spatial resolutions. To show that the ANN results (estimated SAVI values from SAR variables) can be used to predict actual ground-based measures of above-ground phytomass, regression analyses were used with field-sampled values of above-ground phytomass collected for previous research [9].…”
Section: Vegetation Modelingmentioning
confidence: 79%
“…Vegetation is very limited in arctic environments, especially in the High Arctic bioclimatic zones [1,2]. The limited vegetation that is present, however, can have significant effects on the terrestrial carbon balance [3,4] and methane fluxes [5]. Further, knowledge of vegetation density is important for monitoring forage quality and quantity for ungulates such as Peary Caribou (listed as Endangered in the Canadian Species At Risk Act) and muskoxen [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the relationships of the spectral characteristics of the vegetation cover with CO 2 fluxes measured using the chamber technique have been conducted relatively rarely till now (Boelman et al, 2003;Dagg and Lafleur, 2010;Perez-Priego et al, 2015). However, considering that both chamber and spectral measurements can be performed at a small scale of crop fields where the EC technique cannot be applied, our aim was to demonstrate how these two methods can be successfully combined to develop simple empirical models which allow estimation of the GEP and NEP of different crops with remote sensing.…”
Section: Introductionmentioning
confidence: 99%
“…The NDVI, which is proved to directly relate to the land cover condition, is applied to estimating primary productivity. The possibility of predicting average primary productivity by its regression relationship with NDVI has been observed in the Arctic tundra (Boelman et al, 2003) and in steppe ecosystems (Wylie et al, 2003). NDVI tends to be saturated when biomass increases to a high value (Myneni et al, 1995;Hao et al, 2008), this being especially obvious in evergreen forest area (Rahman et al, 2001).…”
Section: Carbon Flux Related Ecosystem Servicesmentioning
confidence: 99%